1100=9879h+h2

Rewrite the equation as 9879h+h2=1100.

9879h+h2=1100

To remove the radical on the left side of the equation, square both sides of the equation.

9879h+h22=11002

Multiply the exponents in ((9879h+h2)12)2.

Apply the power rule and multiply exponents, (am)n=amn.

(9879h+h2)12⋅2=11002

Cancel the common factor of 2.

Cancel the common factor.

(9879h+h2)12⋅2=11002

Rewrite the expression.

(9879h+h2)1=11002

(9879h+h2)1=11002

(9879h+h2)1=11002

Simplify.

9879h+h2=11002

Raise 1100 to the power of 2.

9879h+h2=1210000

9879h+h2=1210000

Move 1210000 to the left side of the equation by subtracting it from both sides.

9879h+h2-1210000=0

Factor the left side of the equation.

Let u=h. Substitute u for all occurrences of h.

9879u+u2-1210000

Factor 9879u+u2-1210000 using the AC method.

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -1210000 and whose sum is 9879.

-121,10000

Write the factored form using these integers.

(u-121)(u+10000)

(u-121)(u+10000)

Replace all occurrences of u with h.

(h-121)(h+10000)

Replace the left side with the factored expression.

(h-121)(h+10000)=0

(h-121)(h+10000)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

h-121=0

h+10000=0

Set the first factor equal to 0 and solve.

Set the first factor equal to 0.

h-121=0

Add 121 to both sides of the equation.

h=121

h=121

Set the next factor equal to 0 and solve.

Set the next factor equal to 0.

h+10000=0

Subtract 10000 from both sides of the equation.

h=-10000

h=-10000

The final solution is all the values that make (h-121)(h+10000)=0 true.

h=121,-10000

h=121,-10000

Solve for h 1100 = square root of 9879h+h^2